Experimental and theoretical XPS and NEXAFS studies of N-methylacetamide and N-methyltrifluoroacetamide. Issue 3 (22nd December 2015) - Li, Cui; Salén, Peter; Yatsyna, Vasyl; Schio, Luca; Feifel, Raimund; Squibb, Richard; Kamińska, Magdalena; Larsson, Mats; Richter, Robert; Alagia, Michele; Stranges, Stefano; Monti, Susanna; et al.
Abstract : Experimental and theoretical spectra of N -methylacetamide and N -methyltrifluoroacetamide at the K-edges are reported. Abstract : Experimental Near-Edge X-ray Absorption Fine-Structure (NEXAFS) spectra of N -methyltrifluoroacetamide (FNMA), which is a peptide model system, measured at the C, N, O and F K-edges are reported. The features in the spectra have been assigned by Static-Exchange (STEX) calculations. Using the same method, we have also assigned previously measured NEXAFS spectra of another peptide model system, N -methylacetamide (NMA). To facilitate the NEXAFS feature assignments, X-ray Photoelectron Spectroscopy (XPS) measurements for NMA and FNMA have been carried out with the aim of obtaining the 1s electron ionization potentials, which are compared with the values predicted by our Hartree–Fock (ΔHF) and Multi Configuration Self Consistent Field (ΔMCSCF) calculations. We also demonstrate an approach to compensate for screening effects that are neglected in the STEX method. Ion yield measurements of FNMA associated with the excitation of several C, N, O, and F K-shell pre-edge resonances have revealed site-specific fragmentation in some cases which we interpret with the aid of our theoretical calculations.